MEDICAL PROBLEMS OF SOCIAL ORPHANHOOD - D.I. Zelinskaya ("Paediatrician" Publishers LLC, 2009)
Social orphanhood is and actual problem of the present, affecting all spheres of social life. There are over 1 million of children, practically devoid of parental care in Russia, and it we take account a phenomenon of latent orphanhood, the problem seems to be much more dimensioned. The system of social health has resources for the influence on the question of saving of family education or finding of family by children with chronic diseases, disorders in development, invalids, and children from boarding schools of different departments, including children's homes. Main task of departments of health service are prophylaxis of early disavowals from children, timely revelation of risk factors of social orphanhood in families, modernization of activity of children's houses in the field of creation of conditions of family education, and more wide use of all types of family formations.Key words: children, orphanhood, invalids.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):5-9)